The Role of dietary supplements in the treatment of asthma - a narrative review - Kozicz, Michał Andrzej; Kołodziej, Magdalena; Saiuk, Nazarii; Mądry, Wojciech; Marcicka, Justyna; Mazurkiewicz, Aleksandra; Salasa, Weronika; Wojciechowska, Adriana; Seredyński, Tomasz; Męczyńska, Joanna (Journal of Education, Health and Sport, 2024)
Introduction: Asthma is a common inflammatory disease of airway affecting both adults and children. In a large number of cases asthma remains poorly controlled. There is a need to find an additional therapeutic demeanour alleviating symptoms and lowering the risk complications in a long-term. Recently, increasing number of studies has been examining dietary supplements in regards to their anti-inflammatory, immunomodulatory, anti-remodelling properties and their use in asthmatic patients. Aim of the Study: The aim of the study was to collect and analyse current literature regarding influence of different dietary supplements on the course of asthma in both adults and children. Methods and Materials: Extensive research was conducted using PubMed and Google Scholar, with the primary focus on literature from the past 5 years. Firstly, potential dietary supplements affecting course of asthma were collected. The names of the substances were juxtaposed with term “Asthma” to gather data regarding their effect on occurrence and control of asthma and potential mechanisms responsible for it. Additionally, references from selected articles were included in the analysis. Results: Dietary supplements show promising results in decreasing asthma symptoms and lowering inflammation of airway. However, our study revealed that in current state of knowledge there is a deficit of studies performed on humans, especially large-scale, prospective studies that assess the efficacy of different doses of dietary supplements. Thus, further research of dietary supplements in asthma is needed, especially large-scale randomised controlled trials.